2017
DOI: 10.17722/jorm.v7i2.184
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y Muslim Female and Male Decision Making Styles in Malaysia: Are They Different?

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Although students are unemployed, they are dependent on parental support and study loans, making them a lucrative market segment. University students are in a transition from university, thus marketers need to shape the potential customers' shopping behaviour before they enter the job market and are earning their income (Aliman et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although students are unemployed, they are dependent on parental support and study loans, making them a lucrative market segment. University students are in a transition from university, thus marketers need to shape the potential customers' shopping behaviour before they enter the job market and are earning their income (Aliman et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…University students in current time, who are Gen Y, have the knowledge and confidence to use the Internet extensively and are the early adopters of new technologies. It is also pertinent to note the influence of the university students have on their families' purchase decisions (Aliman et al, 2017). The students hold the key to their families spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the term CSI was coined, the concept was tested in different regions on target audiences. In beginning, Sprotles and Kendall (1986) tested the concept on American students, then Hafstrom, Chae, and Chung (1992) investigated Korean students; Hiu, Siu, Wang, and Chang (2001) worked on Chinese, Lysonski, Durvasula, and Zotos (1996) worked on Greek, Likewise Patel, Vila-López, and Kuster-Boluda (2013) used Indian sample; tested concept on Germans; Bates (1998) used British sample; Radder, Li, and Pietersen (2006) examined Thrikish sample; Kavas and Yesilada (2007) investigated South African students and more recently Aliman, Ariffin, and Hashim (2017) tested the CSI concept on Malay culture and pointed towards the future exploration of this concept in other cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is evident to argue that religion plays a vibrant role in consumer decision making. Scholars have advised to examine CSI from cultural and religious perspective (Aliman et al, 2017;Kamaruddin & Kamaruddin, 2009). Hafstrom et al (1992) suggested that more research work in this area is needed.…”
Section: Introductionmentioning
confidence: 99%